2020
DOI: 10.3892/mmr.2020.11063
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between autophagy, apoptosis and endoplasmic reticulum stress induced by melatonin in osteoblasts by septin7 expression

Abstract: Melatonin secreted by the pineal body is associated with the occurrence and development of idiopathic scoliosis. Melatonin has a concentration-dependent dual effect on osteoblast proliferation, in which higher concentrations can inhibit osteoblast proliferation and induce apoptosis; however, the underlying mechanism remains unclear. in the present study, flow cytometry was used to demonstrate that osteoblast cells treated with melatonin exhibited significantly increased early and late stage apoptotic rates as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
(44 reference statements)
1
3
0
Order By: Relevance
“…These results further confirm that the induction of autophagy-dependent survival always precedes the irreversible apoptotic cell death upon ER stress [105][106][107]. This theoretical analysis was experimentally proven with many research groups by using various human cell lines and ER stressors [41,105,[114][115][116].…”
Section: Autophagy Always Precedes Apoptosis Upon Er Stresssupporting
confidence: 76%
“…These results further confirm that the induction of autophagy-dependent survival always precedes the irreversible apoptotic cell death upon ER stress [105][106][107]. This theoretical analysis was experimentally proven with many research groups by using various human cell lines and ER stressors [41,105,[114][115][116].…”
Section: Autophagy Always Precedes Apoptosis Upon Er Stresssupporting
confidence: 76%
“…One potential protective mechanism of MLT on blood glucose levels is mediated by MT1 and MT2 receptors-mediated regulation of GLUT4 expression and post-translational modification of the insulin substrate, in turn activating insulin signaling (Cipolla-Neto et al, 2014). We have recently demonstrated that treatment of the human fetal osteoblastic cell line hFOB 1.19 induces ERS and autophagy at an early stage which promotes survival, while at later stages there might be interaction between ERS and autophagy, in turn inducing apoptosis (Cui et al, 2020). However, in a high glucose environment, whether melatonin would affect ERS in osteoblasts is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of MEL in combination with ABT-737 (0.2 µM) on the membrane potential and ROS production was estimated. Since there is a relationship between apoptosis, autophagy and ER stress [ 27 ], we investigated the change in markers for ER stress and autophagy in our experimental conditions.…”
Section: Introductionmentioning
confidence: 99%